Research progress on the effect of mechanical force stimulation on bone metabolism - JIANG Xue; WANG Zuolin (Kouqiang hemian waike zazhi)
The impact of mechanical force stimulation on bone metabolism is currently garnering significant scholarly interest. As scientific inquiry progresses, the focus of these studies has increasingly shifted towards a more granular level of analysis. Recent years, researchers are now examining this phenomenon from various perspectives, including the influence of differing mechanical properties, force magnitudes, frequencies, cell types, and underlying molecular mechanisms on bone metabolism. Given the intricate nature of this process, this article seeks to provide a comprehensive overview of the advancements in research pertaining to the modulation of bone metabolism through the alteration of mechanical stimuli or the targeting of specific cell types and receptors, in order to provide a reference for further research.